Alat Ukur Kesiapan Menikah - Wahidha, Dais Nurul; Dyana Putri, Multynisari; Safira Maharani, Ella Maurizka; Ruhaena, Lisnawati (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Readiness for marriage is an ability that every individual must have, because having readiness for marriage will help individuals to prepare themselves to overcome marriage problems in the future. This research was conducted with the aim of creating a measuring tool for marriage readiness. The research method used was a mixture of qualitative and quantitative methods. In the qualitative stage, 4 participants aimed to explore the theme of marriage readiness. Meanwhile, in the quantitative stage there were 208 people with the aim of identifying psychometric properties (validity test and reliability test). Qualitative data was analyzed using open coding data techniques. Meanwhile, quantitative data was analyzed using content validity tests from expert judgment and construct validity tests using factorial validity with exploratory factor analysis (EFA). The reliability test in this study used Cronbach's Alpha with a reliability coefficient of 0.626. The results of the EFA Test show that there are new factors that can be used as a benchmark for marriage readiness, consisting of 8 factors and 18 items. Based on these psychometric tests, this marriage readiness measuring tool can be used to measure the level of marriage readiness of people in Indonesia.